Case report: Single-operator peroral cholangioscopy system (SpyGlass) diagnosis of an extrahepatic biliary cystadenoma (video) - Deng, Xin; Wang, Jingwen; Mou, Tong; Pan, Long; Du, Chengyou; Wu, Qiao (Frontiers in Medicine, 2023)
Biliary cystadenoma is a type of rare liver cystic tumor. Intrahepatic biliary cystadenomas are the most common, while extrahepatic biliary cystadenomas are rarely seen. Biliary cystadenoma tends to occur in middle-aged to older women and there is a lack of specific preoperative diagnostic markers. Recent advancements in technology and the development of the SpyGlass system have led to an increased use of cholangioscopy. Herein, we report a patient in whom a space-occupying lesion was found in the bile duct by SpyGlass, and who later underwent radical surgery. The pathology report indicated that the final diagnosis was biliary cystadenoma. SpyGlass cholangioscopy may be a novel and effective diagnostic method for biliary cystadenoma.